2021
DOI: 10.3390/ma14143781
|View full text |Cite
|
Sign up to set email alerts
|

Durability Study on High-Performance Fiber-Reinforced Mortar under Simulated Wastewater Pipeline Environment

Abstract: The acid–alkaline-inducd corrosive environments inside wastewater concrete pipelines cause concrete structural deterioration and substantial economic losses all over the world. High-performance concrete/mortar (HPC) was designed to have better resistance to corrosive environments, with enhanced service life. However, the durability of HPC in wastewater pipeline environments has rarely been studied. A high-performance mortar mixture (M) reinforced by supplemental materials (including fly ash and silica fume) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Moreover, the temperature disturbance caused by the cycle of the four seasons or the alternation of day and night is inevitable for the material. The thermal cycling is the prime environmental factor for the dimensional stability of materials [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the temperature disturbance caused by the cycle of the four seasons or the alternation of day and night is inevitable for the material. The thermal cycling is the prime environmental factor for the dimensional stability of materials [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It is conditionally possible to divide the studies conducted by other authors by grouping them into several groups of factors. For example, some authors [12,15,[18][19][20][23][24][25]34,36] were engaged in research aimed at improving the corrosion resistance of cement-based concrete, which are the most traditional type of concrete in current construction but are not environmentally friendly and cheap, leaving a high carbon footprint and not in line with the modern ESG agenda. Other authors [7][8][9][10][11]22,27,29,31,35] were engaged in developing compositions of geopolymer concrete aimed at improving the mechanical properties of such concrete: their strength and improvement of deformation properties.…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [24], the authors carried out experimental and information modeling to optimize the mechanical properties of an alkali-activated solution made with different concentrations of fly ash, granulated blast-furnace slag, and nano-silica from waste glass.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 2 ] The presence of these substances combined with free water can cause severe corrosion problems in oil and gas pipelines, even in fiber‐reinforced composites. A study of fiber‐reinforced mortar has shown that the component responsible for corrosion failures appears to be the fibers rather than the resin, [ 3 ] with the resin playing a protective role by shielding the fibers from the corrosive environment. In composites where the peripheral matrix material was damaged and the fibers were exposed to a corrosion environment, [ 4 ] corrosion spread rapidly throughout the material leading to complete failure of the composite.…”
Section: Introductionmentioning
confidence: 99%